1997
DOI: 10.1165/ajrcmb.16.3.9070604
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils as a source of matrix metalloproteinase-9 in asthmatic airway inflammation.

Abstract: Bronchial asthma is characterized by eosinophil infiltration and tissue remodeling. Matrix metalloproteinases (MMPs) are thought to play critical roles by degradating interstitial matrices in a wide range of lung diseases associated with reorganization of the airway architecture. To investigate whether MMPs are involved in the pathologic processes of bronchial asthma, we examined MMP expression in asthmatic subjects. In situ hybridization revealed abundant expression of MMP-9 (gelatinase B) mRNA in biopsy spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
3
8

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(158 citation statements)
references
References 22 publications
5
142
3
8
Order By: Relevance
“…They are secreted together by bronchial epithelial cells, bind in a 1:1 ratio, and can be modulated by inflammatory mediators and cytokines (16)(17)(18)(39)(40)(41). A high MMP-9͞TIMP-1 ratio in bronchoalveolar lavage fluid indicates collagen degradation, inflammation, and poor prognosis, whereas higher TIMP-1 correlates with tissue repair and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…They are secreted together by bronchial epithelial cells, bind in a 1:1 ratio, and can be modulated by inflammatory mediators and cytokines (16)(17)(18)(39)(40)(41). A high MMP-9͞TIMP-1 ratio in bronchoalveolar lavage fluid indicates collagen degradation, inflammation, and poor prognosis, whereas higher TIMP-1 correlates with tissue repair and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 can be produced by neutrophils, monocytes, macrophages and epithelial cells, and is a marker of lung injury. In addition, there is evidence for eosinophil degranulation in bronchiectasis [22] and eosinophil granules also contain collagenases [23], including MMP-9, which is capable of degrading type IV collagen [24]. Furthermore, release of eosinophil major basic protein (MBP) can induce neutrophil degranulation and IL-8 production [25].…”
Section: Discussionmentioning
confidence: 99%
“…The increased MMP-9 activity observed in the airways of asthmatic patients seems related to an increased number of granulocytes and more precisely neutrophils in the airways rather than to an enhancement of MMP-9 secretion by those cells (Cataldo et al, 2001;Prause et al, 2004). Other authors have suggested that eosinophils, key cells in asthma-related airway inflammation, could also be a major source for MMP-9 in this disease (Ohno et al, 1997). A significant correlation was indeed found in immunohistochemistry and in situ hybridisation between MMP-9 expression and eosinophil counts in bronchial mucosa.…”
Section: Implication Of Mmps In the Pathogenesis Of Asthmamentioning
confidence: 92%
“…A significant correlation was indeed found in immunohistochemistry and in situ hybridisation between MMP-9 expression and eosinophil counts in bronchial mucosa. MMP-9 is also expressed by bronchial epithelium and may be an important factor promoting eosinophilic infiltration into the airways from patients suffering from asthma (Han et al, 2003;Ohno et al, 1997). Although the interest of investigating a balance between MMP-9 and TIMP-1 would probably be restricted to the pericellular area, some authors have reported an imbalance observed between MMP-9 and TIMP-1 measured in bronchial secretions or bronchoalveolar lavage, with a significant increase of TIMP-1 production when compared to that of MMP-9, thought to favouring extracellular matrix deposition (Mautino et al, 1999;Vignola et al, 1998b).…”
mentioning
confidence: 99%